Carbon effect calculation and upgrading strategy of agricultural land consolidation project in urban edge of Three Gorges Reservoir Area - Yang, Wei; Li, Xiaohua; Li, Weihua; Zhang, Yutao; Zhang, Haizhen; Ran, Yuhe (Frontiers in Chemistry, 2022)
Under the background of promoting the construction of ecological civilization and the goal of carbon peak and carbon neutralization, it is of great significance to explore the measurement method and improvement strategy of the carbon effect of agricultural land consolidation. Based on a quantitative analysis and the whole life cycle of land consolidation, this study constructed a carbon effect accounting and analysis framework of agricultural land consolidation project from three stages of project initiation and design, project implementation, and operation management. Taking the agricultural land consolidation project in the Shiyan town on the urban edge of the Three Gorges Reservoir Area as a case, this study made empirical analysis and calculation and analyzed the carbon effect and influencing factors in different consolidation stages. The results showed that the overall carbon effect in the project area was a carbon source. The net carbon emission generated by the project construction was 8358t, which was mainly from workers input and concrete carbon emission; the carbon storage brought about by the adjustment of land use structure was 2,378.20t, which mainly came from the carbon storage increment of newly cultivated land; the carbon storage generated by the agricultural ecosystem was 1,100.04t, which was mainly based on the increase of cultivated land and the improvement of cultivated land quality; the carbon emission from agricultural production activities was 18.18t. Research conclusions: ① the carbon source effect of engineering construction is obvious. Artificial input and concrete are the main carbon sources in the hilly area at the edge of the metropolis; ② the adjustment of land use structure is manifested as a carbon sink effect, which mainly comes from the contribution of carbon storage of newly increased cultivated land; ③ the carbon effect of project operation and management may be a carbon source in the short term, and the long-term effect should be exerted; and ④ based on the concept of whole life cycle, promoting ecological land consolidation, optimizing project design, reasonably arranging consolidation projects, and strengthening operation management are effective measures to improve the carbon effect of land consolidation projects, which are conducive to the realization of the “double carbon” goal.